Articular cartilage of the knee 3 years after ACL reconstruction: A quantitative T2 relaxometry analysis of 10 knees. (3rd September 2015) - Bae, Ji-Hoon; Hosseini, Ali; Wang, Yang; Torriani, Martin; Gill, Thomas J; Grodzinsky, Alan J; Li, Guoan
Abstract : Background and purpose — T1ρ or T2 relaxation imaging has been increasingly used to evaluate the cartilage of the knee. We investigated the cartilage of ACL-reconstructed knees 3 years after surgery using T2 relaxation times. Patients and methods — 10 patients with a clinically successful unilateral ACL reconstruction were examined 3 years after surgery. Multiple-TE fast-spin echo sagittal images of both knees were acquired using a 3T MRI scanner for T2 mapping of the tibiofemoral cartilage. T2 values of the superficial and deep zones of the tibiofemoral cartilage were analyzed in sub-compartmental areas and compared between the ACL-reconstructed and uninjured contralateral knees. Results — Higher T2 values were observed in 1 or more sub-compartmental areas of each ACL-reconstructed knee compared to the uninjured contralateral side. Most of the T2 increases were observed at the superficial zones of the cartilage, especially at the medial compartment. At the medial compartment of the ACL-reconstructed knee, the T2 values of the femoral and tibial cartilage were increased by 3–81% compared to the uninjured contralateral side, at the superficial zones of the weight-bearing areas. T2 values in the superficial zone of the central medial femoral condyle differed between the 2 groups (p = 0.002). Interpretation — The articular cartilage of ACL-reconstructed knees, although clinically satisfactory, had higher T2 values in the superficial zone of the central medial femoral condyle than in the uninjured contralateral side 3 years after surgery. Further studies are warranted to determine whether these patients would undergo cartilage degeneration over time.